The Role of Communication and Mass Media in the Diffusion Process of the Covid-19 Vaccination Program Innovation - Yuda Havid Yudistira; Widiastuti Nela (Kanal: Jurnal Ilmu Komunikasi, 2022)
This study aims to determine the process of innovation diffusion in the Covid-19 vaccination program. The Diffusion of Innovations was chosen because the Covid-19 vaccination program is an innovation or new idea in the health sector. In its distribution, the role of interpersonal communication and the role of the mass media are very influential so that this program can be conveyed to the public and make the public finally become more knowledgeable about the Covid-19 vaccination program. This study uses a qualitative descriptive method with an innovation diffusion theory approach. The informant determination technique used in this study was purposive sampling. Based on the results of the study, it can be concluded that the Covid-19 vaccination program carried out by the government for the community can be conveyed and accepted by the community. The success of this vaccine program is supported by the factor of the role of interpersonal communication which is always carried out with the closest people and the surrounding community so that a lot of knowledge and information can be obtained. Then with the role of the mass media which always spreads and provides information quickly about the Covid-19 vaccination program and the mass media sometimes provides information about the Covid-19 vaccination program in various unique and creative ways so that people are interested and eventually want to be vaccinated.